2013
DOI: 10.1080/08929882.2013.798993
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Recovering Uranium from Seawater by a Braided Polymer Adsorbent System

Abstract: This article provides an independent cost estimate for uranium production from seawater through the braid-type adsorbent recovery system proposed by the Japan Atomic Energy Agency (JAEA). Production costs were developed with standard engineering cost estimation techniques using vendor data and plant design and operational data. The analysis includes life cycle discounted cash flows, economies of scale, and propagation of uncertainties. A reference case based on the Japan Atomic Energy Agency assessment, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(93 citation statements)
references
References 5 publications
2
86
2
3
Order By: Relevance
“…This value is significantly higher compared to that of amidoxime-based adsorbent material. The cost of six-cycle usage of amidoxime-based adsorbent materials to extract the same amount of uranium (1200 tons/y) was 397 million USD [42]. If the usage cycle of the activated carbon electrode is increased, the total cost of chemicals and materials is expected to be lower.…”
Section: Chemical and Materials Cost Assessmentmentioning
confidence: 99%
“…This value is significantly higher compared to that of amidoxime-based adsorbent material. The cost of six-cycle usage of amidoxime-based adsorbent materials to extract the same amount of uranium (1200 tons/y) was 397 million USD [42]. If the usage cycle of the activated carbon electrode is increased, the total cost of chemicals and materials is expected to be lower.…”
Section: Chemical and Materials Cost Assessmentmentioning
confidence: 99%
“…Cost estimates have been performed on the technology and procedures needed to extract uranium from seawater [12]. The estimates have shown that seawater extraction is considerably more expensive than traditional mining methods.…”
Section: Seawater Extractionmentioning
confidence: 99%
“…After, using point results of better efficiency in terms of grams per kilogram obtained in the laboratory, prices were reduced accordingly and announced between 300 to 600 USD/kgU. More recent cost analyses have been made by the Japanese and also by the American Department of Energy [7,10]. The prices quoted are then between 1,000 and 1,400 USD/kgU.…”
Section: Cost Analysismentioning
confidence: 99%
“…The mathematical model is thus used to significantly reduce costs when going from 2 g/kg to 4 and then 6 (the last test presented in 2013 [8,10] had reached 3.3 g/kg in 8 weeks of immersion, 2.6 higher than the previous).…”
Section: Cost Analysismentioning
confidence: 99%
See 1 more Smart Citation